Adoption of Fintech Services for Sharia Bank Users in Indonesia: An Extended TAM Approach - Pahlevi, Reza; Zulpahmi, Zulpahmi; Al-Azizah, Ummu Salma; Hasibuan, Anni Aisyah (EQUILIBRIUM, 2023)
This study proposes a technology acceptance model (TAM) in combination with perceived risk, brand image, sharia compliance, and government support as factors that determine trust to analyze how users adopt fintech services. The research method uses a quantitative approach using non-probability sampling technique. A structured questionnaire was distributed to active customers of Islamic banks in Indonesia, and 357 respondents who met the standards participated. A structural equation model (SEM) was used in the data analysis to test the hypotheses regarding all latent variables and their relationships. The results of the study show that usefulness, ease of use, and brand image of fintech services significantly influence users' attitudes toward fintech adoption. However, trust, perceived risk, and government support do not significantly influence users' attitudes toward adopting fintech. Moreover, attitude and shariah compliance have a significant effect on users' intention to adopt fintech services. This study adds to the existing literature on fintech service adoption by providing a comprehensive overview of the determinants of user attitudes by combining the concepts of trust in fintech services with TAM.